Increasing but Variable Trend of Surface Ozone in the Yangtze River Delta Region of China - Tang, Keqin; Zhang, Haoran; Feng, Weihang; Liao, Hong; Hu, Jianlin; Li, Nan (Frontiers in Environmental Science, 2022)
Surface ozone (O3) increased by ∼20% in the Yangtze River Delta (YRD) region of China during 2014–2020, but the aggravating trend is highly variable on interannual time and city-level space scales. Here, we employed multiple air quality observations and numerical simulation to describe the increasing but variable trend of O3 and to reveal the main driving factors behind it. In 2014–2017, the governmental air pollution control action plan was mostly against PM2.5 (mainly to control the emissions of SO2, NOx, and primary PM2.5) and effectively reduced the PM2.5 concentration by 18%–45%. However, O3 pollution worsened in the same period with an increasing rate of 4.9 μg m−3 yr−1, especially in the Anhui province, where the growth rate even reached 14.7 μg m−3 yr−1. After 2018, owing to the coordinated prevention and control of both PM2.5 and O3, volatile organic compound (VOC) emissions in the YRD region has also been controlled with a great concern, and the O3 aggravating trend in the same period has been obviously alleviated (1.1 μg m−3 yr−1). We further combined the precursor concentration and the corresponding O3 formation regime to explain the observed trend of O3 in 2014–2020. The leading O3 formation regime in 2014–2017 is diagnosed as VOC-limited (21%) or mix-limited (58%), with the help of a simulated indicator HCHO/NOy. Under such condition, the decreasing NO2 (2.8% yr−1) and increasing VOCs (3.6% yr−1) in 2014–2017 led to a rapid increment of O3. With the continuous reduction in NOx emission and further in ambient NOx/VOCs, the O3 production regime along the Yangtze River has been shifting from VOC-limited to mix-limited, and after 2018, the mix-limited regime has become the dominant O3 formation regime for 55% of the YRD cities. Consequently, the decreases of both NOx (3.3% yr−1) and VOCs (7.7% yr−1) in 2018–2020 obviously slowed down the aggravating trend of O3. Our study argues that with the implementation of coordinated regional reduction of NOx and VOCs, an effective O3 control is emerging in the YRD region.